Representing the Irish emigrant: humour to pathos? - Cullen, Fintan (Taylor & Francis, 2017)
The nineteenth-century artist, Erskine Nicol (1825–1904) is well known for his anecdotal and humorous paintings of Irish themes. This article analyses one of his larger oils to show that on occasion he attempted a more serious representation of the rural Irish figure which asks for empathy as opposed to ridicule. The focus is on An Irish Emigrant Landing in Liverpool (signed and dated 1871; Scottish National Gallery). A key part of the analysis is an exploration of the relationship between the painting and a published account of a visit to England by the Irish emigrant depicted.